The Importance of Robotic Process Automation (RPA) on Customer Experience in the South African Financial Sector - Mndebele, Thandekile (University of the Witwatersrand, Johannesburg, 2023)
Robotic process automation (RPA) is a technology that enables businesses to automate repetitive business functions that are considered mundane in order to boost productivity and reduce expenses. Digital transformation, more specifically RPA, has received increased attention in the financial sector because of its potential to improve user and customer satisfaction. This study investigates how RPA affects customer experience in the financial sector in South Africa. A quantitative research approach was used in the study, which included an analysis of the data collected from 215 South African participants against a review of the current existing literature on the RPA subject matter. According to the results, the variables that drive RPA adoption can enhance the customer experience by increasing perceived usefulness, boosting reliability and availability, increasing perceived security, and enhancing perceived ease of use. However, RPA adoption is still in the early stages in the South African financial sector, and there are a number of obstacles to it, including concerns about data and job security. Additionally, to increase the adoption rates in order for financial services providers to fully gain the benefits of RPA, the businesses will need to confront the adoption barriers and make the necessary investments in infrastructure and resources. This study adds to the understanding of how RPA can enhance the customer experience within the financial sector and offers insightful intelligence to any South African business already making use of or considering to use RP
A research report submitted in partial fulfillment of the requirements for the degree of Master of Business Administration to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2023
Keywords: Robotic Process Automation (RPA); RPA adoption; Net Promoter Score (NPS); Reliability and availability; Perceived usefulness; Security; Customer experience; UCTD; SDG-8: Decent work and economic growth